2018
DOI: 10.31086/tjgeri.2018240429
|View full text |Cite
|
Sign up to set email alerts
|

Hip Fracture Surgery in Patients Older than 90 Years: Evaluation of Factors that Affect 30-Day Mortality in a Particularly Risky Group

Abstract: Introduction: Osteoporosis in men is often underdiagnosed and neglected compared to postmenopausal women. Major risk factors should be determined to prevent this disease, which has potential risk of mortality and morbidity for elder men. This study's purpose was to determine the risk factors for osteoporosis and osteopenia in male patients aged >60 years.Materials and Method: Between January 2015 and June 2017, male patients aged >60 years admitted to our centers who underwent dual energy x-ray absorptiometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Various patient-related factors have been reported to be correlated with mortality in the postoperative first year, including advanced age, high preoperative ASA score, obesity, comorbid diseases and postoperative intensive care requirement. [18][19][20][21][22][23] In parallel with the literature, the findings of our study suggested that having two or more comorbidities was a risk factor for mortality in the first year postoperative. On the other hand, no significant correlation was established be- tween age, preoperative ASA score, postoperative intensive care requirement, obesity and duration of hospitalization and mortality in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Various patient-related factors have been reported to be correlated with mortality in the postoperative first year, including advanced age, high preoperative ASA score, obesity, comorbid diseases and postoperative intensive care requirement. [18][19][20][21][22][23] In parallel with the literature, the findings of our study suggested that having two or more comorbidities was a risk factor for mortality in the first year postoperative. On the other hand, no significant correlation was established be- tween age, preoperative ASA score, postoperative intensive care requirement, obesity and duration of hospitalization and mortality in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Hip fractures have been considered as one of the most important causes of mortality and increased hospitalization associated with the discipline of orthopedics and traumatology in the elderly (1,2,14) .…”
Section: Discussionmentioning
confidence: 99%
“…Hip fractures are among the most important causes of death associated with orthopedics and traumatology in the elderly (1,2) . The hip fractures have become more common worldwide due to aging of the population (3) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation